KESAN MAKNA DAN PERUBAHAN MAKNA GAIRAIGO DALAM RUBRIK FASHION MAJALAH SEVENTEEN - Elisabeth, Chatarina (Humanis; Volume 15. No.3. Juni 2016)
The usage of gairaigo could be found in many Japanese mass media for instance, fashion magazines. Fashion magazines are the most active user of gairaigo instead of newspaper and other mass media. In Japanese fashion magazines, gairaigo can be found in advertisements of almost all products. SEVENTEEN as a famous Japanese fashion magazine for female teenagers  has used many gairaigo in their fashion rubric and most gairaigo were derivered from English. The aim of this study is to understand the difference meaning between gairaigo and wago and find out the semantic change of gairaigo that collected from Fashion Rubric in Japanese SEVENTEEN Magazine.
Keywords: gairaigo, meaning, semantic change